Antioxidant Activity, Inhibition α-Glucosidase of Ethanol Extract of Strychnos nitida G. Don and Identification of Active Compounds - Stefani Dhale Rale; Hasim Hasim; Syamsul Falah (Current Biochemistry, 2018)
This study aims to find the treatment of diabetes using natural materials by exploring plants in the province of East Nusa Tenggara. his research was conducted out by extracting the Strychnos nitida G.Don stem using a method of maceration by ethanol 70%. Ethanol extract was then fractionated using n-hexane and ethyl acetate. Simplicia from maceration and fractionation results were then tested for antioxidant activity, α-glucosidase inhibition activity and identification of active compounds. The results showed that ethyl acetate fraction had the lowest IC50 value of 86.83 μg / ml. Results of the α-glucosidase activity test showed that ethyl acetate fraction and n-heksan fraction at 900 ppm had the highest percentage of inhibition of 34.23% and 33.89%. Identification using LCMS/MS method showed that ethyl acetate fraction consist of Benzenemethamine, N, N-dioctyl- as an antioxidantcompound and compound 24-methyl-5-cholestone-hexol as an antidiabetic compound. From the results of this study, we concluded that the extract of kayu ular Strychnos nitida G.Don stem has inhibition activity toward α-glucosidase enzyme.